2018
DOI: 10.1007/s11920-018-0931-x
|View full text |Cite
|
Sign up to set email alerts
|

Which Comes First? An Examination of Associations and Shared Risk Factors for Eating Disorders and Suicidality

Abstract: Individuals with anorexia nervosa, bulimia nervosa, and binge eating disorder experience elevated rates of suicidality compared to the general population. Suicide risk is higher when eating disorders occur with other psychological conditions. Additionally, genetic factors, emotion dysregulation, trauma, stressful life events, and lack of body regard may have roles in the development of both eating disorders and suicidality. Much of the risk for suicidality in eating disorders appears to be driven by comorbid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 83 publications
1
39
0
Order By: Relevance
“…However, because these studies are cross‐sectional, it is possible that suicide risk may increase ED symptoms, that ED symptoms may increase suicide risk, or that ED symptoms and suicide risk are bidirectionally related. Thus, many have argued that the directionality of the relation between ED symptoms and suicide attempts should be more carefully examined (Smith, Ortiz, Forrest, Velkoff, and Dodd, ; Smith, Velkoff, Ribeiro, & Franklin, ; Smith, Zuromski, & Dodd, ; Witte et al., ), but no study yet has directly done so. Therefore, the goal of the current study was to examine bidirectional, longitudinal relationships between ED symptoms and two determinants of suicide ideation—thwarted belongingness (TB) and perceived burdensomeness (PB)—within a sample of individuals with EDs.…”
mentioning
confidence: 99%
“…However, because these studies are cross‐sectional, it is possible that suicide risk may increase ED symptoms, that ED symptoms may increase suicide risk, or that ED symptoms and suicide risk are bidirectionally related. Thus, many have argued that the directionality of the relation between ED symptoms and suicide attempts should be more carefully examined (Smith, Ortiz, Forrest, Velkoff, and Dodd, ; Smith, Velkoff, Ribeiro, & Franklin, ; Smith, Zuromski, & Dodd, ; Witte et al., ), but no study yet has directly done so. Therefore, the goal of the current study was to examine bidirectional, longitudinal relationships between ED symptoms and two determinants of suicide ideation—thwarted belongingness (TB) and perceived burdensomeness (PB)—within a sample of individuals with EDs.…”
mentioning
confidence: 99%
“…Because past research has indicated that EDs precede suicidality (Smith, Ortiz, et al, 2018) and empirical data suggest that expressive suppression may be uniquely related to both disordered eating and suicidal ideation (Forkmann et al, 2014;McLean et al, 2007;Svaldi et al, 2010), we sought to test a mediation model with expressive suppression as a mediator between disordered eating and suicidal thoughts and behaviors. We predicted that expressive suppression would mediate this link.…”
Section: Current Studymentioning
confidence: 99%
“…Although comorbid psychopathology and genetic factors contribute to the association between disordered eating and suicidality (Wade, Fairweather-Schmidt, Zhu, & Martin, 2015;Yao et al, 2016), these factors do not account for all of the variances in the relation. Thus, an investigation of other possible shared risk factors is needed to better understand the potentially deadly association between disordered eating and suicidality (Smith, Ortiz, Forrest, Velkoff, & Dodd, 2018). One risk factor that is shared by both disordered eating and suicidality, along with other anxiety and mood disorders (Hofmann, Sawyer, Fang & Asnaani, 2012), is emotion dysregulation.…”
mentioning
confidence: 99%
“…Eating disorders (EDs) are complex, multifactorial, and severe disorders characterized by altered eating behavior often associated with other psychopathological symptoms and comorbidities such as depression, obsessive–compulsive disorders, perfectionism, anxious personality, suicide attempts (Bulik et al, ; Martinussen et al, ; Miotto et al, ). The etiology of these disorders is presumed to be influenced by developmental, social, and biological processes (Smith, Ortiz, Forrest, Velkoff, & Dodd, ). Dieting behavior is quite common in industrialized countries throughout the world where the Western ideals of thinness and cultural attitudes for physical shape are predominant.…”
Section: Introductionmentioning
confidence: 99%